Congenital myasthenia syndrome in a Chinese family with mutations in MUSK: A hotspot mutation and literature review. (June 2020) - Liu, Yiqi; Qiao, Kai; Yan, Chong; Song, Jie; Huan, Xiao; Luo, Sushan; Lu, Jiahong; Zhao, Chongbo; Xi, Jianying
Highlights: Two cases of late onset CMS with a homozygous hotspot mutation, c.308A > G in MUSK were presented. Patients with nonsense, frameshift and splicing mutations showed a more severe phenotype. The clinical features of patients with a homozygous c.308A > G mutation were proposed. Abstract: Congenital myasthenic syndrome (CMS) caused by mutations in MUSK is very rare and the genotype-phenotype relationship in MUSK related CMS is still unclear. Here we identified two patients carrying a homozygous hotspot mutation, c.308A > G in MUSK from a Chinese family. Both of them presented predominant bulbar weakness and atrophy of bilateral temporalis and masticatory muscles. To address the phenotype-genotype relationship, a total of 27 MUSK related CMS patients were reviewed. Patients with nonsense, frameshift or splicing mutations showed earlier onset (10/13 vs 2/14 neonatal onset, p = 0.0018) and more occurrence of vocal cord paralysis or stridor (8/13 vs 0/14, p = 0.0006), indicating a more severe phenotype. Comparing with patients carrying other missense mutations, the four patients carrying a homozygous c.308A > G mutation showed the female predominance (4/10 vs 4/4) and dramatic exacerbation after emotional or physiological stresses (2/10 vs 4/4) like pregnancy, menstrual periods and infection. All these indicated a genotype-phenotype relationship in MUSK -related CMS.